2016
DOI: 10.1590/1807-1929/agriambi.v20n11p1031-1035
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and substrate on Plukenetia volubilis L. seed germination

Abstract: A B S T R A C TThe objective of this work was to evaluate the effect of temperature and substrate on the germination of P. volubilis seeds. Seeds harvested from 25 matrix plants were submitted, in two studies, to conditions of (i) sowing in rolled paper towel at the temperatures of 10, 15, 20, 25, 30, 35, 40, and 45 °C, for the evaluation of germination, first count of germination, germination speed index and mean time for germination, and (ii) sowing in the substrates paper towel, sand, Bioplant®, Bioplant® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
2
7
0
2
Order By: Relevance
“…The results obtained in this study agree with those reported by Silva et al (2016), who also evaluated germination of oleaginous seeds, such as Plukenetia volubilis L., where the maximum germination percentage occurred after sowing on paper roll at 25 ºC. However, Jeromini et al (2018) reported that the maximum germination rate of P. volubilis seeds, as occurred with those of H. sabdariffa L. var.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The results obtained in this study agree with those reported by Silva et al (2016), who also evaluated germination of oleaginous seeds, such as Plukenetia volubilis L., where the maximum germination percentage occurred after sowing on paper roll at 25 ºC. However, Jeromini et al (2018) reported that the maximum germination rate of P. volubilis seeds, as occurred with those of H. sabdariffa L. var.…”
Section: Resultssupporting
confidence: 90%
“…Lighter substrates, such as sand and vermiculite, allow greater gas exchange and better drainage, reducing the physical barrier to initial seedling development (Jeromini et al, 2018), as observed for P. volubilis by Silva et al (2016). It is noteworthy that the plantmax ® substrate has macro and micronutrients in its composition, as well as suitable particle quality, these led to favorable results for all H. sabdariffa seed evaluated variables, because just after the H. sabdariffa seed germination and emission of the primary roots, immediately began the process of absorption of the nutrients present in this substrate and its mobilization to the seedling structures, promoting their development and dry mass accumulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of emergence rate are consistent with those from Scalon and Jeromini (2013), who evaluated the emergence velocity of Eugenia pyriformis and found the highest values for substrate latosol + Bioplant® at 75% of WRC. The presence of organic matter and sand in the substrates may have improved emergence velocity, since they both might enable greater gas exchange and better drainage, as well as reduce the physical barrier to initial development of the seedling (SILVA et al, 2016).…”
Section: Discussionmentioning
confidence: 99%